Improving Personal and Social Information Management with Advanced Tagging - Mirzaee, Vanesa; Razavi, Maryam Najafian; Iverson, Lee (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper describes an innovative tagging model incorporated into a web 2.0 social and personal information management application. Our work utilizes web 2.0 tagging concepts in a new way in an effort to provide better support for users’ needs for contextualization and personalization of their information spaces for both personal… Cet article décrit un modèle innovateur d’étiquetage intégré à une application de gestion de l’information personnelle et sociale du Web 2.0. Notre travail utilise les concepts de l’étiquetage du Web 2.0 d’une manière nouvelle, afin de mieux subvenir aux besoins des utilisateurs pour la contextualisation et la personnalisation de leurs espaces informationnels, pour des fins personnelles…